2019
DOI: 10.25255/jbm.2019.7.2.111.136
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Mediating Role of Organizational Learning Capability on the Effect of Transformational Leadership on Entrepreneurial Orientation

Abstract: Leadership plays a significant role in directing the organization, recognizing environmental needs and paving the way for appropriate development. Among the various styles of leadership, one of the most popular for managing change is transformational leadership. The purpose of this paper is to reviewing the literature and the associations among transformational leadership, entrepreneurial orientation, and organizational learning capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 108 publications
(132 reference statements)
1
6
0
Order By: Relevance
“…Therefore, hypothesis 1 (i.e., TL has a positive impact on organisational learning capability) is confirmed. This result is in line with the previous studies in which researchers found that a firm’s leadership have a positive influence on organisational learning capability (Aragón-Correa et al, 2007; García-Morales et al, 2012; Jamil & Obeidat, 2019; Van der Voet, 2014; Vera & Crossan, 2004). Research findings of Obeidat et al (2018) also revealed that transformational attributes of leaders enhance the intellectual capital of the firm and ultimately improve the learning capability of firms.…”
Section: Results and Findingssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, hypothesis 1 (i.e., TL has a positive impact on organisational learning capability) is confirmed. This result is in line with the previous studies in which researchers found that a firm’s leadership have a positive influence on organisational learning capability (Aragón-Correa et al, 2007; García-Morales et al, 2012; Jamil & Obeidat, 2019; Van der Voet, 2014; Vera & Crossan, 2004). Research findings of Obeidat et al (2018) also revealed that transformational attributes of leaders enhance the intellectual capital of the firm and ultimately improve the learning capability of firms.…”
Section: Results and Findingssupporting
confidence: 93%
“…As a result, they show their risk-taking ability, the third factor of organisational learning (Obeidat et al, 2018). Employees also involve themselves in the fourth crucial factor of organisational learning called participative decision-making when they come to a consensus about choosing the best possible solution/alternative (Jamil & Obeidat, 2019). Lastly, employees interact with stakeholders to build direct contacts and interpret the changes in the external environment.…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
“…Despite being around for decades, the term "entrepreneurship" has yet to have any exact definition (Jamil & Obeidat, 2019). In numerous literatures, the term is defined as "the creation of enterprise", "the creation of innovation", "the creation of employment", "the creation of growth", and "the creation of value".…”
Section: Entrepreneurial Orientation (Ento)mentioning
confidence: 99%
“…The action was taken because Iraq has recognized entrepreneurship as economic growth-driven activity. Consequently, the Iraqi government believed that inspiring entrepreneurs could make them be known as a developed nation globally (Jamil & Obeidat, 2019).…”
Section: Introductionmentioning
confidence: 99%